Political Oratory: The Role of Rhetorical Strategies in Persuading an Audience - Nilufar Babajonova; Aliyeva Muxlisa (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This paper explores the art of political oratory and its role in persuading an audience. It focuses on the rhetorical strategies commonly used in political speeches, particularly the classical elements of logos, ethos, and pathos. Through analysis of speeches by prominent politicians, the study demonstrates how these rhetorical tools are effectively employed to influence public opinion. Additionally, the paper examines the psychological state of the audience, contextual factors, and the structural composition of speeches as key elements in persuasive communication. The study concludes with insights into the rhetorical skills and strategies necessary for becoming an effective political speaker.